The Responsibility to Respect Workers’ Rights in Global Supply Chains - Zbucka-Gargas, Marta (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The purpose of this publication is to identify those responsible for violations of basic labour rights in global supply chains. The free movement of finance capital does not go hand in hand with the protection of human rights, and the possibility of using the work of workers all over the world in production does not guarantee equal treatment in the field of elementary human rights. The weakness of many states, the need for capital investment, the race to keep costs low, and the lack of diligence in complying with the law result in human rights violations. The multitude of actors involved and the jurisdiction of many countries do not create a clear picture of liability. It is necessary to try to assign responsibility to those process participants who are involved in the creation of the supply chain and who benefit financially from it.